Legal Vacuum Regarding the Filling of Regional Heads During the Transition Period of the 2024 Simultaneous Regional Elections - Rustam Rustam; Megawati Barthos (Return : Study of Management, Economic and Bussines, 2024)
This study explores the legal vacuum in filling regional head positions during the transitional period of the 2024 Simultaneous Regional Elections in Indonesia. The transitional period poses challenges in appointing interim regional heads, as existing regulations lack clarity on authority, responsibilities, and legitimacy. This research aims to analyze the gaps in the legal framework and provide recommendations to address these issues. Utilizing normative legal research methods with a statute and conceptual approach, this study examines existing laws and regulations, including Law No. 10 of 2016 and related ministerial regulations. The findings reveal significant limitations in defining the scope of interim officials' authority, creating uncertainty in governance and public trust. The research concludes that the absence of comprehensive regulations impacts regional administration stability, emphasizing the urgency of establishing clear guidelines for interim appointments. By addressing these legal voids, the study offers solutions to ensure effective governance, enhance transparency, and uphold democratic principles during the transitional period.